Prognostic Significance of Signet Ring Cells in Gastric Cancer: The Higher Proportion, The Better Survival - Yang Li (Frontiers Media S.A., 2021)
BackgroundDue to the fact that the definition of gastric signet ring cell cancer (GSRC) was still controversial in the past decades, the prognosis affected by the proportion of signet ring cells within gastric cancer is uncertain. This study compared the clinicopathological features and prognosis of GSRC with the various proportions of signet ring cells.MethodsWe collected GSRC cases without metastasis who underwent curative (R0) resection between 2011 and 2018. Individuals who were in the low-proportion signet ring cell group (LSRC, <50%) were matched to those who were in the high-proportion signet ring cell group (HSRC, >50%) through propensity score matching (1:1). We used Cox proportional hazard regression to calculate the adjusted hazard ratios (HR) and 95% confidence intervals (CI) and explored interactions with gender and stage.ResultsWe had 1:1 matched individuals including 231 cases from the LSRC group and 231 cases from the HSRC group. Patients with HSRC had a significantly higher overall survival rate in the multivariable model (aHR = 0.56, 95%CI = 0.38, 0.84) compared with those with LSRC. The association of HSRC appeared to be more substantial among individuals at early stage and N0 stage (p-interaction < 0.01).ConclusionsThis study confirms that GSRC with different proportions of signet ring cells could affect the survival of the patient. Further clinical studies should be developed in the future to provide an appropriate treatment strategy for GSRC.